Trauma's Influence on the Main Character's Identity and Relationships in Hillenbrand's Novel Unbroken - Kholiq Akbar As'ari; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This study examines the profound impact of wartime trauma on the protagonist’s post-war social identity and relationships as depicted in Laura Hillenbrand’s literary biography, Unbroken. The research objective is to analyze the psychological and social responses of Louis Zamperini to his experiences as a WWII POW. Using a descriptive qualitative methodology, this research applies Cathy Caruth’s psychoanalytic trauma theory to conduct a close reading of the text. The results indicate that Zamperini’s trauma manifests as classic PTSD symptoms—re-experiencing, avoidance, negative cognition, and hyper-arousal—which lead to alcoholism, aggression, and the near-dissolution of his marriage. The study concludes that Zamperini's healing journey, achieved through forgiveness rather than revenge, illustrates how a survivor can reclaim their social identity by reframing their traumatic narrative. This research contributes to the field by bridging literary analysis with psychological theory, demonstrating how literary biography can serve as a vital text for understanding the long-term social consequences of trauma and the complex path to resilience.